Cardiovascular complications in Covid-19 infected patients: Massive Pulmonary Embolism and Myocardial Infarction with Acute Heart Failure - Case Series Report - Mitevska I; Busletikј O; Gruevа E; Kotlar I; Kandic E (Македонско лекарско друштво = Macedonian medical association, 2021)
Patients with diagnosed COVID-19 infection have an increased risk of thrombotic events and complications, which highly contribute to raised morbidity and morta- lity rate. Inflammation and hypercoagulability caused by infection are responsible for pulmonary embolism and acute myocardial infarction in infected patients. Bed- side focus echocardiography is a very useful noninva- sive imaging method for fast diagnosis in critically ill patients suspected of being infected with COVID -19. We report two cases with acute thrombotic complica- tions as a manifestation of COVID-19 infection. Echo- cardiography and pulmonary CT angiography helped us to properly proceed with patient’s management. Prompt diagnosis and evidence-based management of these conditions are lifesaving. Echocardiography plays an important role in the bedside management of critically ill patients during the COVID-19 pandemic
КАРДИОВАСКУЛАРНИ КОМПЛИКАЦИИ КАЈ COVID-19 БОЛНИ ПАЦИЕНТИ: МАСИВНА БЕЛОДРОБНА ЕМБОЛИЈА И МИОКАРДЕН ИНФАРКТ СО АКУТНА СРЦЕВА СЛАБОСТ – ПРИКАЗИ НА СЛУЧАИ